2017
DOI: 10.1002/art.39844
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Osteoarthritis Severity in Aged Mice With Deletion of Macrophage Migration Inhibitory Factor

Abstract: Objective Macrophage migration inhibitory factor (MIF) is a pro-inflammatory cytokine that is elevated in the serum and synovial fluid of osteoarthritic (OA) patients. In this study, the potential role of MIF in OA was studied using human joint tissues and in vivo in mice with age-related and surgically induced OA. Methods MIF in conditioned media from human chondrocytes and meniscal cells and from cartilage explants was measured by ELISA. Severity of OA was analyzed histologically in male wild-type and Mif−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 46 publications
5
44
0
Order By: Relevance
“…Despite this, we found the protective effect of 4-IPP against bone loss was more potent in the calvarial osteolysis model when compared with the OVX model. This is likely because of the fact that MIF expression is elevated in inflammatory bone conditions such as wear particle-induced osteolysis, osteoarthritis, and rheumatoid arthritis (20,44,45), which may explain the better outcome observed in the calvarial osteolysis model.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, we found the protective effect of 4-IPP against bone loss was more potent in the calvarial osteolysis model when compared with the OVX model. This is likely because of the fact that MIF expression is elevated in inflammatory bone conditions such as wear particle-induced osteolysis, osteoarthritis, and rheumatoid arthritis (20,44,45), which may explain the better outcome observed in the calvarial osteolysis model.…”
Section: Discussionmentioning
confidence: 99%
“…An articular cartilage structure score was also generated as previously described (McNulty et al., 2011), which showed similar results to the Safranin‐O staining score but with less sensitivity to subtle changes in OA progression (data not shown). Slides stained with hematoxylin and eosin were used to assess osteophyte score, with each quadrant graded on a 0–3 scale for osteophyte size as previously described (Rowe et al., 2017). For immunohistochemistry with a primary antibody targeting tdTomato (cat # 600‐401‐379; Rockland Immunochemicals, Limerick, PA) or targeting Mmp‐13 (ab84594; Abcam, Cambridge, UK), antigen retrieval was performed with heated sodium citrate and sections were stained using the VECTASTAIN ® Elite ABC‐HRP kit (Vector Laboratories, Burlingame, CA).…”
Section: Methodsmentioning
confidence: 99%
“…Many studies have shown the prospects of using anti-MIF antibodies in basic research and clinical applications. The inhibition of MIF may cause the reduction of the severity of age-related osteoarthritis in mice [15]. Targeted deletion of MIF gene delays the development of chronic lymphocytic leukaemia and prolongs survival in mice [16].…”
Section: Discussionmentioning
confidence: 99%